Marine Robotics and Applications (Ocean Engineering & Oceanography,, 2018)
This book reports on findings at the intersection between two related fields, namely coastal hydrography and marine robotics. On one side, it shows how the exploration of the ocean can be performed by autonomous underwater vehicles; on the other side, it shows how some methods from hydrography can be implemented in the localization and navigation of such vehicles, e.g. for target identification or path finding. Partially based on contributions presented at the conference Quantitative Monitoring of Underwater Environment, MOQESM, held on October 11-12, 2016, Brest, France, this book includes carefully revised and extended chapters presented at the conference, together with original papers not related to the event. All in all, it provides readers with a snapshot of current methods for sonar track registration, multi-vehicles control, collective exploration of underwater environments, optimization of propulsion systems, among others. More than that, the book is aimed as source of inspiration and tool to promote further discussions and collaboration between hydrographers, robotic specialists and other related communities.